Equitable food value chains through collaborative action [in an inequitable landscape] - Micaela Lipman; Domonique Griffin; Erik Woyciesjes; Gabriella Hall; Samina Raja (Journal of Agriculture, Food Systems, and Community Development)
There is growing scholarly and practitioner interest in applying collective and place-based efforts to create equitable food systems. Drawing on community coalition action theory (CCAT), this paper explores the potential for enhancing food equity through collaborative action across the food value chain. Through a case study of a collaborative initiative to promote equitable food systems, this paper documents the possibilities and pitfalls of collaborative, cohort-based efforts within the inequitable landscape of Buffalo, New York (NY). The paper relies on mixed-methods data that include key informant interviews, participant observations, and surveys of organizations that participated in the Buffalo Community Food System Grant program. Corroborating prior research, we find that initiatives that seek to foster collective action offer unique possibilities for food equity, as well as some key limitations, especially within the context of a racialized food environment. Strengthening food systems by investing in relationships across food value chains opens new avenues for collective action. To promote food equity, new forms of collective action, including functional relationships across the value chain, must address deeper structural imbalances in the food system, such as those resulting from structural racism.